Adopsi Pendekatan Pengembangan Pasar (Market Development) Pada Sub Sektor Kopi Arabika Dataran Tinggi Kabupaten Garut - Dani Hamdan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Arabica coffee in Garut plateau is a smallholder plantation sub-sector that has market growth, but is less balanced with upstream growth. The approach for this sub-sector should be comprehensive covering upstream began with the superior coffee plantations to downstream in form of ready-to-eat coffee products for consumers, in order to increase added value for business actors along the coffee chain. The "market system development" approach is applied as a method that is expected to create attraction and service providers for farmers. This approach is done by providing a stimulus for farmers in form of purchasingmore competitive price of fresh coffee beans, coffee quality sorting, cash payment schemes, and mentoring. Stimulus for service providers is given by a means of revolving fund in purchasing fresh coffee beans, productivity improvement, production efficiency, product standardization and market access. This approach results an uplift and consistency offresh coffee beansquantities from the established farmers. It also increases quality of coffee beans, productivity, efficiency and market access. A total of 158 farmers from five farmer groups of Andalan earned an increased income about 15 percent, 50 percentof productivity at service providers in coffee roasting and 15 percent of efficiency, packaging standardization for two downstream coffee products,  15 percent additional market access, and the creation of two coffee-selling places. At the farmer facilitation level, there have been 10,000 seeds of coffee and fertilizer formulated specifically for coffee plants that can be accessed by farmer groups in a soft loan scheme with the cutting of the fresh coffee beans sales. The "market development" approach has created a fascination for coffee entrepreneurs